Contribución de las TIC para la mejora de la evaluación (2023)
This research article conducts a literature review, which takes into account 12 articles related to information and communication technologies (ICT) and how they influence the evaluation processes, for the purpose of analyzing the contribution of ICT in improving the evaluation processes. The databases consulted for the research of the articles were Scielo, Dialnet, Redalyc and Google Scholar. It is evident that ICTs play an important role in educational practices, because they allow the integration of new methodologies in the classroom to improve the learning process, and they can also be incorporated in the evaluation processes and thus improve the assessment process. This according to articles investigated.